Design, Development and Evaluation of an Automated Low tunnel for Hi-Tech Agriculture - AISWARYA L SHILPA S. SELVAN; Dr. Abdul Hakkim V.M (Guide) (Tavanur 2017 Department of Land & Water Resources and Conservation Engineering)
Design, Development and Evaluation of an Automated Low tunnel for Hi-Tech Agriculture
Design, Development and Evaluation of an Automated Low tunnel for Hi-Tech Agriculture